PCR based detection and analysis of Pasteurella multocida isolates causing haemorrbagic septicaemia in India buffaloes - DUTTA, T K; GAUTAM, RAJEEV; SINGH, V P; KUMAR, A A (The Indian Journal of Animal Sciences, 2014)
In India, haemorrhagic septicaemia (HS) in buffalo is caused by serotype B:2 of Pasteurella multocida. A total of 32 P. multocida isolates from buffalo with the symptoms of HS were tested for their detection by PM-PCR and HSB-PCR assays. Except 1, all the isolates were of serotype B:2 as confirmed by conventional serolyping and HSB-PCR assay. PCR was conducted using various preparations as template DNA for its application in the field conditions. All the 32 isolates were experimentally inoculated in mice and rabbit and the spleen, bone marrow, as well as heart blood were applied as template for both PCR assays after simple processing. Inoculated organisms were reisolated in pure culture from all the experimental animals after death.